Design, modeling and implementation of a novel pitch angle control system for wind turbine. (September 2015) - Yin, Xiu-xing; Lin, Yong-gang; Li, Wei; Gu, Ya-jing; Wang, Xiao-jun; Lei, Peng-fei
Abstract: A novel pitch angle control system is proposed to smooth output power and drive-train torque fluctuations for wind turbine. This system is characterized by an outer open control loop for enhancing the direct pitching motion and an intrinsic hydro-mechanical position control loop offering the benefit of sensor-less pitch control. A pragmatic design procedure is provided and several key design parameters are determined or optimized. Modeling, stability analysis and dynamic characteristics of this pitch control system are also presented. Comparative experimental results have validated the effectiveness and efficiency of this system in power and torque regulations. Highlights: A novel pitch angle control system is proposed. This system is characterized by an outer open loop an intrinsic hydro-mechanical position loop. Sensor-less pitch angle control can be achieved by the proposed system. A pragmatic design procedure is provided for this system.